Pleasure in the Fragments of Aristotle’s Lost Writings - Pacewicz, Artur (Peitho. Examina Antiqua, 2025)
It is well known that Aristotle’s philosophical legacy has not survived in its entirety to our time. A large part of it has been lost, and only scattered fragments, paraphrases and testimonies cited by other ancient philosophers have survived. The analyses carried out in the article focus on what the Stagirite says about pleasure in fragments of lost writings, especially in the Symposium, On Pleasure, Protrepticus and On Justice. The aim of the analyses is to establish whether or not the statements in these fragments can be correlated with statements from Aristotle’s surviving works, and whether or not they are compatible with them. Thanks to the analyses, it is also possible to show that the hypothesis that Aristotle’s philosophy may have been subject to evolution is not tenable at least as far as the doctrine of pleasure is concerned.